Improving Transparency, Integrity, and Accountability in Water Supply and Sanitation : Action, Learning, Experiences - Gonzalez de Asis, Maria; O'Leary, Donal; Ljung, Per; Butterworth, John (Washington, DC: World Bank, 2012)
This manual on improving transparency, integrity, and accountability in water supply and sanitation is the result of a partnership between the World Bank Institute (WBI) and transparency international (TI). It was developed under the open and participatory government program at the municipal level (known by its Spanish acronym as the GAP Municipal Program). This manual can help: 1) increase the involvement of civil society by engaging all stakeholders in setting water supply and sanitation priorities and monitoring performance, including reducing opportunities for corruption; 2) increase the contributions of water supply and sanitation services to poverty reduction by increasing the quality and coverage of service to poorer communities on an equitable basis; 3) promote the financial sustainability of water and sanitation service delivery organizations, thereby increasing the confidence of consumers, civil society organizations, and other stakeholders in those institutions' ability to expand improve service; and 4) raise ethical standards among all stakeholders, especially service delivery organizations, thereby instilling a sense of public service throughout these organizations.